7T MR Safety. Issue 2 (24th August 2020) - Fagan, Andrew J.; Bitz, Andreas K.; Björkman‐Burtscher, Isabella M.; Collins, Christopher M.; Kimbrell, Vera; Raaijmakers, Alexander J.E.; ,
Abstract : Magnetic resonance imaging and spectroscopy (MRI/MRS) at 7T represents an exciting advance in MR technology, with intriguing possibilities to enhance image spatial, spectral, and contrast resolution. To ensure the safe use of this technology while still harnessing its potential, clinical staff and researchers need to be cognizant of some safety concerns arising from the increased magnetic field strength and higher Larmor frequency. The higher static magnetic fields give rise to enhanced transient bioeffects and an increased risk of adverse incidents related to electrically conductive implants. Many technical challenges remain and the continuing rapid pace of development of 7T MRI/MRS is likely to present further challenges to ensuring safety of this technology in the years ahead. The recent regulatory clearance for clinical diagnostic imaging at 7T will likely increase the installed base of 7T systems, particularly in hospital environments with little prior ultrahigh‐field MR experience. Informed risk/benefit analyses will be required, particularly where implant manufacturer‐published 7T safety guidelines for implants are unavailable. On behalf of the International Society for Magnetic Resonance in Medicine, the aim of this article is to provide a reference document to assist institutions developing local institutional policies and procedures that are specific to the safe operation of 7T MRI/MRS. Details of current 7T technology and the physics underpinning its functionality are reviewed, with the aim of supporting efforts to expand the use of 7T MRI/MRS in both research and clinical environments. Current gaps in knowledge are also identified, where additional research and development are required. Level of Evidence 5 Technical Efficacy 2 J. MAGN. RESON. IMAGING 2021;53:333–346.